Gender Differences in Thyroid Function among Euthyroid Subjects with Positive and Negative Thyroid Antibodies (Antibodies to Thyroid Peroxidase and/or Thyroglobulin) - Molodovskaya, I. N.; Tipisova, E. V.; Elfimova, A. E.; Alikina, V. A. (Human physiology, 2023)
The aim of the study was to demonstrate gender differences in thyroid function among euthyroid subjects, that had negative values of antibodies, and euthyroid subjects, that had positive antibodies (antibodies to thyroid peroxidase—AntiTPO and/or antibodies to thyroglobulin—AntiTG). A total of 200 clinically healthy people (85 women and 115 men) were enrolled in this study and classified into groups depending on gender and level of autoantibodies in the blood. Group A (59 women and 100 men) had normal values of thyroid hormones and negative values of antibodies according to the test instructions, i.e. AntiTPO < 50 IU/mL and/or AntiTG < 100 IU/mL. Group B (26 women and 15 men) had normal values of thyroid hormones and positive antibodies, i.e. AntiTPO ≥ 50 IU/mL and/or AntiTG ≥ 100 IU/mL. Serum hormones of the pituitary-thyroid system, thyroglobulin and antibodies concentration was measured by enzyme immunoassay. Analysis of gender differences in thyroid function in individuals with positive thyroid antibodies found statistically significantly higher T4 values in women compared to men. Men with positive antibodies had an insignificant increase in thyroid-stimulating hormone (TSH) levels against the background of a statistically significant decrease in the values of the (T3 + T4)/TSH ratio. Women with positive antibodies were characterized by a statistically significant decrease in thyroglobulin levels. In all analyzed groups, thyroglobulin negatively correlated with AntiTG, and in men of Group B this relationship became stronger. In Group B in both men and women AntiTPO had negative correlation with (T3 + T4)/TSH ratio. Our results indicate that the measurement of thyroid indices, in combination with the determination of serum levels of thyroid autoantibodies and thyroglobulin, may be useful in identifying euthyroid subjects at potential risk of developing thyroid disease and thus be helpful in making early treatment decisions to prevent a prolonged course of the disease.